Book Review Essay: Pitfalls in Storytelling Advice and PraxisThe Springboard: How Storytelling Ignites Action in Knowledge-Era Organizations, by DenningStephen. Boston & Oxford: Butter-worth-Heinemann, 2001.Making Stories: A Practical Guide for Organizational Leaders and Human Resource Specialists, by GargiuloTerrence L.. London & Westport, CT: Quorum, 2002.Tales for Change: Using Storytelling to Develop People and Organizations, by ParkinMargaret. London & Sterling, VA: Kogan Page, 2004.The Story Factor: Inspiration, Influence, and Persuasion Through the Art of Storytelling, by SimmonsAnnette (Foreword by LipmanDoug). Cambridge, MA: Perseus, 2001.Myth-Makers and Story-Tellers, by KayeMichael. Sydney, New South Wales: Business & Professional Publishing, 1996. - Boje, David M. (Academy of Management Review, 2006)
The article reviews several books about management including “The Springboard: How Storytelling Ignites Action in Knowledge-Era Organizations,” by Stephen Denning, “Making Stories: A Practical Guide for Organizational Leaders and Human Resource Specialists,” by Terrence L. Gargiulo, and “Tales for Change: Using Storytelling to Develop People and Organizations, by Margaret Parkin.